Echinostome cercariae from Biomphalaria straminea (Mollusca: Planorbidae) in a ricefield from northeastern Argentina - Fernández, María Virginia (2014)
The species of larval Echinostomatidae that infect Biomphalaria straminea (Dunker, 1848) in a ricefield in Corrientes province, Argentina, were studied. Examination of 5 510 snails during 2 rice cultivation cycles, from December 2010 to May 2011 and from December 2011 to April 2012, revealed the presence of 3 new species: Echinocercaria sp. XIII, Echinocercaria sp. XIV and Echinocercaria sp. XVI in 36 snails (0.65%). The most common species was Echinocercaria sp. XVI. Prevalence of 3 species during the first rice cultivation cycle was low (< 1%), whereas during the second rice cultivation cycle it was somewhat higher, with prevalence greater than 1% only in Echinocercaria sp. XVI. The species of echinocercariae in B. straminea from the agricultural habitat described in the present study are new additions to the species already reported for the genus Biomphalaria in the region.